Auction theory - Krishna, Vijay (San Diego : Academic Press, 2002)
The book discusses the theory of auctions .
Includes bibliographical references (p. [289]-297) and index.
aia 07/05/13
Loan
Keywords: Auctions -- Mathematical models; Game theory